Muslim jurists’ opinions on modern In Vitro Fertilization (IVF) practices: its health and social implications on mothers - Hashi, Abdurezak Abdulahi; Munirah, Sha'ban; Muhammad Radzi, Aa'zamuddin Ahmad (Unique Conferences Canada Publication, 2017)
Fertility is the natural ability to produce offspring or the state of being fertile, which reflects the ability or the natural quality of reproducing animal offspring. In the normal circumstances, fertilization takes place in a natural way, as long as the couple is health, having sexual intercourse and without using preventive measures and practices. However, in the instances in which fertilization cannot be achieved by means of natural intercourse, assisted fertilization by means of artificial insemination and IVF are sought by infertile couples. While fertilization by means of sexual intercourse of married couples seems to be acceptable, fertilization through assisted reproductive techniques and related practices has raised various legal, health social and moral debates across the globe. Like other jurists and legal professionals in the world, Muslim jurists have addressed the legality of artificial insemination as well as health and moral dimensions of assisted reproductive techniques and related practices. They have exhibited a keen interest in this subject, but provided diverse and contrastable opinions on the permissibility of artificial insemination and IVF practices. This paper uses comparative and textual analysis, and aims to address Muslim jurists’ legal opinions on health and social implications of IVF on mothers. In the meantime, the paper aims to compare the legal opinions Muslim jurists to that of their counterparts in elsewhere of the world.